Impact of Irrigation and Fertigation Levels on the Growth and Yield of Elephant Foot Yam (Amorphophallus paeoniifolius (Dennst.) Nicolson) - Venkatesan, K; T., Saraswathi; L., Pugalendhi; P, Jhansi Rani (JOURNAL OF ROOT CROPS, 2015)
Elephant foot yam is gaining popularity as a commercial or cash crop in Andhra Pradesh, West Bengal, Uttar Pradesh, Bihar, Jharkhand and Tripura. Its area is expanding in Tamil Nadu, Gujarat and Maharashtra. However, lack of scientific studies on fertigation hinders its further expansion in the nontraditional and water scarce areas. Judicious and optimal use of water and fertilizers are prerequisites to maximize the productivity and return. Hence, field experiments were carried out at Department of Vegetable Crops, Horticultural College and Research Institute, Tamil Nadu Agricultural University, Coimbatore during 2010-2013 through AICRP on Tuber Crops to standardize drip with fertigation technology for elephant foot yam. The experiment was laid out in factorial RBD and replicated thrice. For standardizing the fertigation system, five irrigation levels (I1-25% cumulative pan evaporation (CPE); I2-50% CPE; I3-75% CPE ; I4-100% CPE and I5-Flood irrigation) and four fertigation levels (F1 - fertigation with 100% recommended dose of fertilizers (RDF); F2-fertigation with 75% RDF; F3-fertigation with 50% RDF and F4-absolute control) were followed.. The greatest plant height (78.89 cm), pseudostem girth (12.29 cm), canopy spread EW (65.58 cm) and NS (64.47 cm) were observed under application of 100% RDF along with flood irrigation. There was significant difference in yield among fertilizer levels and irrigation levels. The highest corm yield (47.66 t ha-1) was observed under application of 100% RDF along with irrigation at 100% CPE.